The effect of board of directors’ characteristics on anti-money laundering: Evidence from banks sector - Elhefni, Ahmed Hesham Moawed; Alnor, Nasareldeen Hamed Ahmed; Al-Matari, Ebrahim Mohammed; Mohammed, Omer Alsir Alhassan; Ahmed, Alsadig (International Journal of Management and Sustainability, 2024)
This study aims to investigate how board composition affects banks’ efforts to combat money laundering. It was an applied research study using a descriptive and correlational design. All banks operate in the Arab world. We used screening procedures to select a sample of banks. The findings indicate the inclusion of board members with expertise in compliance, law, or finance has a favorable effect on financial institutions’ AML initiatives. Board members who have experience in the financial sector or who have specific knowledge of anti-money laundering laws improve the results of anti-money laundering efforts, thereby avoiding fines for their companies. The Board of Director’s knowledge of anti-money laundering legislation, its ability to ensure the bank’s adherence to national and international anti-money laundering laws, and its flexibility in responding to regulatory modifications positively impact the commitment to anti-money laundering. The Board of Directors is the controller of the institution and therefore has the main role in combating money laundering. A board of directors committed to combating money laundering keeps the entire organization compliant and avoids the risks of money laundering.